Peptide Self-Assembled Nanostructures for Drug Delivery Applications. (24th April 2017) - Fan, Taotao; Yu, Xiaoyan; Shen, Bing; Sun, Leming
Abstract : Peptide self-assembled nanostructures are very popular in many biomedical applications. Drug delivery is one of the most promising applications among them. The tremendous advantages for peptide self-assembled nanostructures include good biocompatibility, low cost, tunable bioactivity, high drug loading capacities, chemical diversity, specific targeting, and stimuli responsive drug delivery at disease sites. Peptide self-assembled nanostructures such as nanoparticles, nanotubes, nanofibers, and hydrogels have been investigated by many researchers for drug delivery applications. In this review, the underlying mechanisms for the self-assembled nanostructures based on peptides with different types and structures are introduced and discussed. Peptide self-assembled nanostructures associated promising drug delivery applications such as anticancer drug and gene drug delivery are highlighted. Furthermore, peptide self-assembled nanostructures for targeted and stimuli responsive drug delivery applications are also reviewed and discussed.